3D Manipulation and Imaging of Plant Cells using Acoustically Activated Microbubbles. Issue 3 (8th February 2019) - Läubli, Nino F.; Shamsudhin, Naveen; Vogler, Hannes; Munglani, Gautam; Grossniklaus, Ueli; Ahmed, Daniel; Nelson, Bradley J.
Abstract: The precise manipulation of single cells and organisms opens exciting new possibilities for biological research. In this work, an acoustic rotational manipulation method for imaging single cells of different plant species (pollen grains of Lilium longiflorum and Arabidopsis thaliana ) is demonstrated. Acoustically activated microbubbles generate radiation forces as well as microvortices in the aqueous medium, which allow various specimens to be trapped and precisely rotated. The rotational behavior of individual plant cells is studied and their motion to facilitate 3D fluorescent microscopy is controlled. The use of this manipulation technique for high‐resolution 3D optical reconstructions of nontransparent samples is demonstrated. The applicability of this method for open‐microchannel arrangement, which may enable multiplexed 3D access to samples for microsurgery and injection, is further demonstrated. Abstract : 3D manipulation of single cells and organisms plays a key role in their investigation. The demonstrated rotation and reconstruction of nontransparent single plant cells provides new insights into their morphological features and the use of open microchannels allows novel ways of interactions, as 3D physical access to the specimen is enabled.